Media Freedom and Pluralism - Beata Klimkiewicz (Central European University Press, 2010)
Addresses a critical analysis of major media policies in the European Union and Council of Europe at the period of profound changes affecting both media environments and use, as well as the logic of media policy-making and reconfiguration of traditional regulatory models. The analytical problem-related approach seems to better reflect a media policy process as an interrelated part of European integration, formation of European citizenship, and exercise of communication rights within the Europ...